Effects of maintenance of propofol-ketamine anesthesia with repeat bolus and constant rate infusion of propofol on physiological, biochemical, anesthetic and analgesic indices in dogs (Journal of Advanced Veterinary and Animal Research, 2015)
The  research  work  was  aimed  at  investigating physiological,  biochemical,  analgesic  and  anesthetic indices of dogs anesthetized with propofol-ketamine and  maintained  with  repeat  bolus  and  constant infusions  of  propofol.  Eight  dogs,  assigned  to  two groups (n=4), were used in this study. All dogs were pre-medicated with atropine (at 0.03 mg/kg bwt) and xylazine (at 2 mg/kg bwt). Anesthesia was induced by a  concurrent  administration  of  propofol  (at  4  mg/kg bwt)  and  ketamine  (at  2.5  mg/kg  bwt).  Maintenance of  anesthesia  in  Group  1  was  done  with  a  repeat bolus of propofol (at 2 mg/kg bwt), while in Group 2 it was  done with a constant infusion of propofol (at 0.2  mg/kg  bwt/min).  Gastrotomy  was  performed  in both  groups,  and  anesthesia  was  maintained  for  60 min.  Physiological,  analgesic,  anesthetic  parameters and  plasma  glucose  concentration  were  measured. There was no significant (P>0.05) difference found in the  analgesia  and  pedal  reflex  scores,  durations  of  analgesia  and  recumbency,  recovery  time  and standing  time  between  the  groups.  The  heart  rate, respiratory  rate  and  rectal  temperature  reduced significantly  (P